Ede-2 - Andrey Filchenko; Nadia Fedotova; Sergej Kovylin (Andrey Filchenko, 2014)
Southern Selkup, . river, text recorded in ., by researcher ., from speaker . born in . in Ozernoe village, speaker bi-lingual Selkup-Russian, education - . Archived: Tomsk TSPU Field Archive. Volume C-. pp. Manuscript scanned by J. in 2012; annotated and translated by ., in 2013. Previously .published. Автор текста (рассказчик): . Родился прим. в . г. в . Образование среднее. Жил в . Автор записи (кем записано): .: Записано в . г. в п. ., Томская область. Хранится: Архив ЯНС ТГПУ: Том C-., стр. . Манускрипт оцифрован каф. ЯНС: - сканирование: ., 2012 - набор, глосиирование и перевод: ., 2013 Ранее . публиковался. Comprehensive Documentation & Analysis of two Endangered Siberian Languages: legacy data and last speakers of Eastern Khanty and Southern Selkup Southern Selkup legacy text data. Southern Selkup